Cellular Mechanisms of Spatial Memory Recovery via Hyperbaric Oxygen Therapy in Experimental TBI: A Review - Jaslindo, Lieka Nugrahi; Ibrahim, Nurhadi (Biomedical Journal of Indonesia, 2025)
Traumatic Brain Injury (TBI) impairs spatial memory, affects individuals' quality of life, and increases disability and mortality rates. Hyperbaric Oxygen Therapy (HBOT), which delivers nearly 100% oxygen in a pressurised environment, has a potential intervention to ameliorate these cognitive deficits. This narrative review presents evidence from animal studies demonstrating the efficacy of HBOT in enhancing spatial memory in rats with TBI. Specifically, we present evidence that HBOT increases levels of Brain-Derived Neurotrophic Factor (BDNF) and activates the Hypoxia-Inducible Factor 1-alpha (HIF-1α) pathway. These molecular changes foster neuroplasticity and reduce oxidative stress, thereby promoting the repair and growth of dendritic spines and decreasing Reactive Oxygen Species (ROS) levels to prevent neuronal death. By elucidating these mechanisms, this review shows how HBOT contributes to spatial memory recovery in TBI, suggesting a promising therapeutic avenue that need further clinical exploration to refine treatment protocols and evaluate its applicability in human TBI recovery.